MENINGKATKAN KINERJA KARYAWAN BAGIAN WORKSHOP MELALUI INTERVENSI PELATIHAN DAN STIMULUS KOMPENSASI - Yogie Rahmat; Putra Eka (Eko dan Bisnis: Riau Economic and Business Review, 2026)
Abstract : The research was conducted at PT Toyota Agung Automall Arengka Pekanbaru, located at Jl. Arengka No. 13, Pekanbaru, Riau. The purpose of this study was to determine the partial effect of education, training, and compensation on employee performance in the workshop department of PT Toyota Agung Automall Arengka Pekanbaru, and to simultaneously determine the effect of education, training, and compensation on employee performance in the workshop department of PT Toyota Agung Automall Arengka Pekanbaru. To achieve these objectives, the study used a sample of 53 people using the census method. The data analysis method used multiple linear regression. Based on the test results for the education and training variables, the calculated t-value was greater than the t-table (4.520 > 2.008) and a sig. 0.000 < 0.05. The results of the compensation variable test obtained a calculated t-value > t-table (2.626 > 2.008) and a sig. 0.011 < 0.05. Thus, it can be concluded that education, training, and compensation partially influence employee performance at PT Toyota Agung Automall Arengka Pekanbaru. The most dominant factors influencing employee performance are education and training. Recommendations include improving or at least maintaining education and training variables, which are measured using needs assessments. Ensuring that employees are motivated to master the content of education and training, creating a learning environment, ensuring that trained employees apply the content, selecting or selecting education and training methods, and evaluating education and training programs. Although the company sometimes does not fully involve employees in providing education and training, this is understood by employees.